TINJAUAN HUKUM: HUBUNGAN KERJA KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA BERDASARKAN UU NO. 6 TAHUN 2014 TENTANG DESA - Prabowo, Andrianto; Handayani, Tri Astuti (Jurnal Hukum Ius Publicum, 2024)
This research aims to determine the working relationship between the Village Head and the Village Consultative Body based on Law no. 6 of 2014 concerning Villages. Seeing the importance of the village government system which must be carried out based on applicable regulations. This research method was carried out using normative legal research using a statutory approach. The Legislative Regulations Approach is an approach that looks at and analyzes statutory regulations relating to village government which is the subject of research. The data in this research is secondary data in the form of laws. The research results found that village government law, in accordance with Law Number 6 of 2014, confirms the partnership between the Village Head and the Village Consultative Body (BPD). Villages have the authority to regulate government affairs and community interests. The Village Head is responsible for governance and development, while the BPD plays a role in drafting village regulations, gathering community aspirations, and supervising the performance of the village head. The Village Law and related regulations regulate the roles and authorities of both to prevent conflict. This collaboration is regulated in Village Regulations to ensure the effectiveness of tasks and prevent conflicts. BPD is also involved in managing village funds and democracy, making an important contribution to holistic and transparent village development.